STRESS AS PREDISPOSING FACTOR OF SOME CHRONIC DISEASES INCLUDING PERIODONTAL DISEASE - Dewi-Nurul; Hayatun-Safrina H (Faculty of Dentistry, Universitas Indonesia, 2006)
Stress is hypothesized as a common pathway for several related chronic diseases of man. Psychosocial stress as modified by perceptions and coping by patients can lead to physical processes. Psychoneuroimmunologic (PNI) studies have suggested that psychosocial stress can alter immune function and increase vulnerability to illnesses. The patients also have high sensitivity to periodontal disease (PD). This article describes the association of stress as a physiological response to diseases such as PD, rheumatoid arthritis (RA), and inflammatory bowel disease. The psychosocial stress can lead to physiological processes through 1) the hypothalamic-pituitary-adrenal (HPA) axis leading to glucocortico-steroid secretion; 2) the autonomic nervous system, resulting in the release of catecholamine; or 3) the hypothalamic-pituitary-gonadal axis, resulting in the release of sex hormones. These processes may affect chronic diseases. It can be concluded that psychosocial stress in periodontal disease patients must be considered and social support must be provided in order to achieve an optimum periodontal therapy result.